IMPLEMENTASI MODEL PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN KETRAMPILAN SOSIAL SISWA - Nunuk Suryani (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Collaborative learning is a philosophy and lifestyle interaction that makes cooperation as an interaction structure. This structure is designed to facilitate achieve common goals collectively. In every situation, when several people are in a group, the collaboration was a way to deal with mutual respect and appreciate the capabilities and contributions of each member of the group. In it there is division of authority and revenue responsibilities among the group members to carry out the action of group. The main idea underlying the collaborative learning is a consensus built up through cooperation among group members as opposed to a competition which put the benefits of the individual. The collaborative learning practitioners utilize this philosophy in the classroom, in committee meetings, in various communities, in families and is widely as a way of living with and interacting with others.Collaborative learning needs to be applied in schools. Collaborative ways of learning is more moving or encourage students to a active and interactive as well as cooperation in completing academic tasks in the classroom. Thus, collaborative learning is fundamentally different from conventional-traditional approach has been done, the better,